Keutel Syndrome: A Case Report With Aortic Calcification - Ayyıldız, Pelin; Bılgıcı, Meltem Ceyhan; Ozyılmaz, Berk; Sungur, Metin; Baysal, Kemal; Ogur, Gonul (Fırat University, 2012)
Keutel Syndrome is a rare autosomal recessive syndrome. Laryngotracheobronchial calcification is a rare finding in young children and can occur in Keutel syndrome. Here we report 6 years old female patient with laryngotracheobronchial and aortic calcification and also review and discuss the clinical features of the syndrome. Concentric calcification of hepatic, renal, coronary and cerebral arteries were mentioned in Keutel Syndrome but to the best of our knowledge no previous aortic calcification was reported.

Keutel sendromu nadir görülen, otozomal resesif bir hastalıktır. Küçük çocuklarda nadir görülen laringotrakeobronşiyal kalsifikasyon nedenlerinden biridir. Bu vakada laringotrakeobronşiyal ve aort kalsifikasyonu olan 6 yaşında kız hastayı sunmayı ve beraberinde Keutel sendromunun klinik bulgularını gözden geçirmeyi amaçladık. Bilgilerimize göre literatürde Keutel sendromlu hastalarda hepatik, renal, koroner ve serebral arterlerde kalsifikasyonlar rapor edilmiştir ancak aort kalsifikasyonu daha önce rapor edilmemiştir.
Keutel Sendromu: Aort Kalsifikasyonu Olan Bir Vaka Sunumu